Working in the Service Sector - Bosch, Gerhard 1947-; Lehndorff, Steffen 1947- (Taylor and Francis, 2005)
The rise to prominence of the service sector - heralded over half a century ago as the great hope for the twenty-first century - has come to fruition. In many cases, employment in the service sector now outnumbers that in manufacturing sectors, and it is accepted that in all developed countries, the service sector is the only one in which employment will grow in future. The reasons for this is the subject of much controversy and debate, the outcomes of which are not merely of academic interest but of decisive importance for economic policy and the quality of working and living conditions in future. In order to examine these various arguments, research teams from eight European countries worked together for three years on a comparative study of the evolution of service sector employment in EU member states. They also investigated working and employment conditions in five very different service industries (banking, retailing, hospitals, IT services and care of the elderly) in a number of countries, and the results of their research are presented in this informative new collection, of interest to students academics and researchers involved in all aspects of industrial economics
Keywords: Arbeit; Dienstleistungssektor